The synthesis of oseltamivir phosphate key intermediate, tert-butyl (5-(pentan-3-yloxy)-6- ((trimethylsilyl)oxy)cycloh ex-3-en-1-yl)carbamate and synthesis of (1S,2S)- hydroxycyclohexene-1,2,3- triazole derivatives / Sufi An-Nur Abd Haris - Abd Haris, Sufi An-Nur (2022)
Oseltamivir phosphate also known as Tamiflu is an active neuraminidase inhibitor for the treatment of influenza A and B. In this study, a new method on synthesizing a key intermediate of oseltamivir phosphate was established by using commercially available 1,4-cyclohexadiene as the starting materials. In the first part, tert-butyl (5-(pentan-3- yloxy)-6-((trimethylsilyl)oxy)cyclohex-3-en-1-yl)carbamate 14 (Tamiflu intermediate) was synthesized from 1,4-cyclohexadiene via epoxidation using m-CPBA to give cyclohexene epoxide 8, followed by epoxide ring opening with trimethyl silane azide using Salen catalyst complex to afford azide 9 and 10. Then the azide 9 was reduced by using Pd(OH)2/C and the resulted amine was protected with ditert-butyldicarbonate to give 11 and 12, followed by allylic oxidation of 11 with SeO2 and TBHP to afford 13. The compound 14, was synthesized via etherification reaction of dialcohol 11 with 3- pentanol catalyzed by BF3.OEt2 with the overall yield of 13%. The second part focused on the synthesis triazole derivatives 15a-15d using azide 10 as the starting material via click reaction employing iodocopper CuI[P(OEt)3] complex in toluene to afford triazole derivatives 15a-15d with the yield of 17- 29%. Both oseltamivir phosphate key intermediate and triazole derivatives explore new synthetic approaches towards the development of new chemicals for bioactivity purposes